Radikalisme di Kalangan Terdidik - Nurlaila, Nurlaila (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2018)
There are many factors that cause a person to act radically. Socio-political changes and economic conditions are considered to be a number of factors why a person becomes radical. Religion is used as legitimacy for every action carried out. At present, radical ideology has penetrated the world of education. Although it is not yet at an alarming stage, it has great potential to damage existing social order. This paper briefly reviews the development of radical ideology, the concept of jihad and acts of terrorism in Indonesia along with alternative treatments for educated circles. The method used in this research is library research.